Empirical testing of the Arbitrage Pricing Theory using data from the Johannesburg Stock Exchange - M. J. Page (South African Journal of Business Management, 1986)
In 1976 Stephen A. Ross developed a new theory of securities pricing called the Arbitrage Pricing Theory (APT). According to the APT the return an investor can expect from a share is related to the risk-free rate and numerous other factors rather than just the return on the market as predicted by the Capital Asset Pricing Model (CAPM). Although a considerable amount of empirical research has been carried out into the APT in the United States of America, little appears to have been done in South Africa In this article empirical research is carried out into the APT using data from the JSE. The research involves both attempting to establish the number of 'priced' factors influencing risky security returns on the JSE and comparing the explanatory ability of the APT and CAPM. Factor analysis is used to establish the number of 'priced' APT factors and regression analysis is used to assess the explanatory ability of the models. The findings suggest that at least two factors determine security returns, rather than just the return on the market as predicted by the CAPM, and that a two-factor APT model has significantly better explanatory powers than the CAPM in an ex-post sense. Finally, it is apparent that considerably more empirical research needs to be done if the factors are to be conclusively identified and checked for stability through time.
Keywords: 650